Women's Access to Rural Credit and Micro Finance in West Bengal - Das, Sulagna; Patnaik, B.C.M. (Indian Journal of Finance, 2016)
The present paper examined the status of women in the state of West Bengal on the basis of microfinance. The paper is based on secondary data collected from published trend analysis report of NABARD from the year 2009-10 to the year 2014. The study was conducted on four types of banks, namely public sector banks, private sector banks, regional rural banks, and cooperative banks taken as the independent variable ; savings amount, total loan disbursed amount, outstanding loan amount were considered as the dependent variables. An attempt was made in the present study to analyze the data related to microfinance for women in the state of West Bengal by using a statistical tool, MANOVA. The analysis of the data found out that there is significant mean variation between the three variables of the four types of banks.